Randomized trial comparing cyanoacrylate embolization and radiofrequency ablation for incompetent great saphenous veins (VeClose) - Morrison, Nick; Gibson, Kathleen; McEnroe, Scott; Goldman, Mitchel; King, Ted; Weiss, Robert; Cher, Daniel; Jones, Andrew (Journal of vascular surgery, 2015)
Whereas thermal ablation of incompetent saphenous veins is highly effective, all heat-based ablation techniques require the use of perivenous subfascial tumescent anesthesia, involving multiple needle punctures along the course of the target vein. Preliminary evidence suggests that cyanoacrylate embolization (CAE) may be effective in the treatment of incompetent great saphenous veins (GSVs). We report herein early results of a randomized trial of CAE vs radiofrequency ablation (RFA) for the treatment of symptomatic incompetent GSVs. Two hundred twenty-two subjects with symptomatic GSV incompetence were randomly assigned to receive either CAE (n = 108) with the VenaSeal Sapheon Closure System (Sapheon, Inc, Morrisville, NC) or RFA (n = 114) with the ClosureFast system (Covidien, Mansfield, Mass). After discharge, subjects returned to the clinic on day 3 and again at months 1 and 3. The study's primary end point was closure of the target vein at month 3 as assessed by duplex ultrasound and adjudicated by an independent vascular ultrasound core laboratory. Statistical testing focused on showing noninferiority with a 10% delta conditionally followed by superiority testing. No adjunctive procedures were allowed until after the month 3 visit, and missing month 3 data were imputed by various methods. Secondary end points included patient-reported pain during vein treatment and extent of ecchymosis at day 3. Additional assessments included general and disease-specific quality of life surveys and adverse event rates. All subjects received the assigned intervention. By use of the predictive method for imputing missing data, 3-month closure rates were 99% for CAE and 96% for RFA. All primary end point analyses, which used various methods to account for the missing data rate (14%), showed evidence to support the study's noninferiority hypothesis (all P < .01); some of these analyses supported a trend toward superiority (P = .07 in the predictive model). Pain experienced during the procedure was mild and similar between treatment groups (2.2 and 2.4 for CAE and RFA, respectively, on a 10-point scale; P = .11). At day 3, less ecchymosis in the treated region was present after CAE compared with RFA (P < .01). Other adverse events occurred at a similar rate between groups and were generally mild and well tolerated. CAE was proven to be noninferior to RFA for the treatment of incompetent GSVs at month 3 after the procedure. Both treatment methods showed good safety profiles. CAE does not require tumescent anesthesia and is associated with less postprocedure ecchymosis.